The challenge of the university training environmentalization - Bilert, Vania Silva de Souza (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
For a long time the environmental issues were addressed in isolation, with respect to social, economic, cultural factors, among others. However, in recent decades the concern with environmental issues began to insert themselves into curricular areas of several educational institutions, notably the University. In this sense, the objective of this study is to analyze how the incorporation of environmental issues in the process of university education in the spheres of education, research and extension occurs. The study is characterized as a case study with a qualitative approach, and data collection was conducted through interviews. As a locus of research, we selected a state public university of Paraná. The results indicated that the environmental discussion in the university is still a new process, filled with challenges and desires of the individuals involved, but that is initiating the demands for environmental training.